2019
DOI: 10.1016/j.sleep.2019.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of a custom-made Narval mandibular repositioning device for the treatment of obstructive sleep apnea: ORCADES study 2-year follow-up data

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 50 publications
(65 reference statements)
0
4
0
2
Order By: Relevance
“…Long-term oral appliance use can cause tooth movement, change in bite, and temporomandibular joint (TMJ) discomfort. However, several recent studies have shown that oral appliance therapy was associated with no significant tooth movement over a period of several years [29]. These side effects are rare and manageable with the proper selection of an oral appliance and patient follow-up [30].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term oral appliance use can cause tooth movement, change in bite, and temporomandibular joint (TMJ) discomfort. However, several recent studies have shown that oral appliance therapy was associated with no significant tooth movement over a period of several years [29]. These side effects are rare and manageable with the proper selection of an oral appliance and patient follow-up [30].…”
Section: Discussionmentioning
confidence: 99%
“…Obstructive Sleep Apnea Syndrome (OSAS) is a breathing disorder that occurs during sleep, which is relatively common and easily overlooked [1] . At present, it is believed that OSAS may cause irreversible damage to the function of multiple systems of the whole body and significantly impact the cardiac function of patients.…”
Section: Introductionmentioning
confidence: 99%
“…This CPAP therapy is also the gold standard in AHI reduction, as it improves the patient's quality of life, reduces the risk of motor vehicle accidents, and reduces cardiovascular events and mortality associated with OSA. However, between 30% and 50% of patients prescribed CPAP fail to maintain long-term adherence [8,9].…”
Section: Introductionmentioning
confidence: 99%